Internal coherence in the Degree in Business Administration and Management: Learning Outcomes as a governance tool - E.I. Cano Montero; J. Chamizo González; T. Martín Vecino (Universitat Politècnica de València, 2016)
Learning outcomes (LO) and its assessment as quality and governance indicators in the Higher Education (HE) Curricula, are very present in the international quality standards for HE. Assuring the internal coherence of the required elements to reach LO is currently a challenge for HE institutions. A study was conducted in the Degree in Business Administration and Management in Talavera (GADE) during the course 2012-2013 with the aim of analyzing the unit guides (UG) to assess the intra-competences coherence in the so called "verified curricula" and its corresponding learning activities, identifying the most practiced competences by doing the learning activities.The paper reveals by mean of the unit guides the range of criteria used to link learning activities with competences, contributing to detect incoherencies that allow working on improvement proposals for next courses. It is also revealed that UG are a key element in the assessment and improvement of the curricula's quality. This paper comprises of several parts, starting with the framework for assessing and monitoring of the degrees, followed by the theoretical aspects of LO as coherence indicators for the curricula, then the competences developed are analyzed and tabulated by year, unit and so on, finally the findings are discussed and conclusion delivered.